2010
DOI: 10.1002/hbm.21006
|View full text |Cite
|
Sign up to set email alerts
|

Functional deactivations: Multiple ipsilateral brain areas engaged in the processing of somatosensory information

Abstract: Somatosensory signals modulate activity throughout a widespread network in both of the brain hemispheres: the contralateral as well as the ipsilateral side of the brain relative to the stimulated limb. To analyze the ipsilateral somatosensory brain areas that are engaged during limb stimulation, we performed functional magnetic resonance imaging (fMRI) in 12 healthy subjects during electrical median nerve stimulation using both a block- and an event-related fMRI design. Data were analyzed through the use of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 63 publications
(117 reference statements)
11
40
1
2
Order By: Relevance
“…In support of this interpretation, sensorimotor and posterior insula clusters identified specifically in the neutral contrast showed lower signal change differences when compared with the aversive interaction (see Figure 2b; Supplementary Table S2). These are consistent with relative deactivations (eg, see Hayes and Huxtable, 2012) previously noted in the somatosensory cortex surrounding the primary site of activation (related to the threat of shock on the left ankle in this case) as well as ipsilateral to it (Drevets et al, 1995;Klingner et al, 2011).…”
Section: Aversive Context Interaction Bold Activitysupporting
confidence: 90%
“…In support of this interpretation, sensorimotor and posterior insula clusters identified specifically in the neutral contrast showed lower signal change differences when compared with the aversive interaction (see Figure 2b; Supplementary Table S2). These are consistent with relative deactivations (eg, see Hayes and Huxtable, 2012) previously noted in the somatosensory cortex surrounding the primary site of activation (related to the threat of shock on the left ankle in this case) as well as ipsilateral to it (Drevets et al, 1995;Klingner et al, 2011).…”
Section: Aversive Context Interaction Bold Activitysupporting
confidence: 90%
“…The findings of our study about a hyperventilation-induced hypocapnia during speech tasks should also be considered in the controversial debate about the physiological origin and significance of BOLD decreases (negative BOLD responses (NBRs)) during task performances found in both humans (Allison et al, 2000;Bressler et al, 2007;Hamzei et al, 2002;Hashimoto and Sakai, 2003;Hlushchuk and Hari, 2006;Kastrup et al, 2008;Klingner et al, 2011;Laurienti et al, 2002;Liu et al, 2011;Newton et al, 2005;Northoff et al, 2007;Pasley et al, 2007;Schäfer et al, 2012;Shmuel et al, 2002;Smith et al, 2004;Stefanovic et al, 2004;Tootell et al, 1998) and animals (Alonso Bde et al, 2008;Boorman et al, 2010;Harel et al, 2002;Kennerley et al, 2012;Schridde et al, 2008;Shmuel et al, 2006). As pointed out by Boorman et al (2010), NBRs are often observed but less frequently reported in fMRI studies.…”
Section: Which Causes An Increase In Sto 2 [O 2 Hb] [Thb] and An Dmentioning
confidence: 69%
“…Deactivation was significantly decreased in the TLE group relative to the controls when listening to the story, and the subgroup analyses at a low Z-score threshold suggest that the EEG neg subgroup showed significantly increased deactivation relative to the controls and the EEG pos subgroup. This could suggest that deactivation is not only a sign of haemodynamic redistribution (Woolsey et al 1996;Harel et al 2002) but it may also reflect neuronal inhibition as it has been proposed (Stefanovic et al 2005;Kobayashi et al 2006;Northoff et al 2007;Kastrup et al 2008;Klingner et al 2011) and this is seen particularly strongly in patients with normal interictal EEG. When the inhibitory mechanisms break down and/or they are overtaken by the epileptiform discharges and excitation, positive BOLD response becomes detectable in the thalamocortical networks and is also detected as an abnormal interictal EEG.…”
Section: Discussionmentioning
confidence: 87%